Neuroprotective effects of crude extracts, compounds, and isolated molecules obtained from plants in the central nervous system injuries: a systematic review - Moura, Maria Vitoria Nava; Mesquita da Conceição Bahia, Gabriel; Gonçalves Correa, Marcio; Araujo Sarges, Maíza Amanda; Lobão, Thaís Alves; Sanches, Erica Miranda; Oliveira, Karen R. H. Matos; Herculano, Anderson Manoel; Bahia, Carlomagno Pacheco (Frontiers in Neuroscience, 2023)
The number of people with central nervous system (CNS) injuries increases worldwide and only a few therapies are used to mitigate neurological damage. Crude extracts, compounds, and isolated molecules obtained from plants have neuroprotective effects; however, their actions on the central nervous system are still not fully understood. This systematic review investigated the neuroprotective effects of crude extracts, compound, and isolated molecules obtained from plants in different CNS lesions. This PICO (Population/Problem, Intervention, Control, Outcome) systematic review included in vivo and in vitro studies that used small rodents as experimental models of CNS injuries (P) treated with crude extracts, compounds, and/or isolated molecules obtained from plants (I), compared to non-intervention conditions (C), and that showed a neuroprotective effect (O). Fourteen out of 5,521 studies were selected for qualitative analysis. Several neuroprotective effects (improvement of antioxidant activity, modulation of the inflammatory response, tissue preservation, motor and cognitive recovery) in the brain and spinal cord were reported after treatment with different doses of crude extracts (10 studies), compounds (2 studies), and isolated molecules (2 studies). Crude extracts, compounds, or isolated molecules obtained from plants showed promising neuroprotective effects against several CNS injuries in both the brain and spinal cord, regardless of gender and age, through the modulation of inflammatory activity and oxidative biochemistry, tissue preservation, and recovery of motor and cognitive activity.